The Politics of Space: A Reflection on Remapping - Bethell-Bennett, Ian A (International Journal of Bahamian Studies, 2018)
Sea bathing shall be permitted at or from the public property between the western boundary of the British Colonial Hotel and Nassau Street between the hours of 9 a.m. and 12 noon and 4 p.m. and 6 p.m. only. (“Sea Bathing Rules,” 1938) Finally we’re inside The gated community Finally with Massa inside The gated community Savages singing the blues Safe within the pink wall (Manoo-Rahming, 2010, p. 79) Place and space are vital ingredients to Caribbean success in tourism. Space and how we live in it is historically and politically or geopolitically determined beyond our lives. The Bahamas and Puerto Rico share a particular resonance as their spaces are being repacked and re-commercialized as parts of an elite geographical zone where the rich come to play and stay but avoid the crowds. So, public spaces, the coast and beaches, are being taken as privately owned and rezoned spaces for high-end enjoyment. In the last two decades, this privatization of space has taken over in Puerto Rico and The Bahamas in disturbing and interesting ways. Many locals buy into the offer of jobs in exchange for international development or Foreign Direct Investment as government eases its way out of governance in the wake of climate-change-powered super hurricanes and the resultant green gentrification. So, while small coastal communities succumb to the dream of progress couched in land sales and increased land prices, local access to regular lives disappears under high-end gated communities and private islands.